2002
DOI: 10.1095/biolreprod.102.006833
|View full text |Cite
|
Sign up to set email alerts
|

Potential Importance of Vitrification in Reproductive Medicine

Abstract: As early as 1985, ice-free cryopreservation of mouse embryos at -196 degrees C by vitrification was reported in an attempted alternative approach to cryostorage. Since then, vitrification techniques have entered more and more the mainstream of animal reproduction as an alternative cryopreservation method to traditional slow-cooling/rapid-thaw protocols. In addition, the last few years have seen a significant resurgence of interest in the potential benefits of vitrification protocols and techniques in human-ass… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
131
0
18

Year Published

2004
2004
2018
2018

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 237 publications
(150 citation statements)
references
References 98 publications
1
131
0
18
Order By: Relevance
“…Recently, vitrification has been widely used to cryopreserve oocytes in many mammals (Kono et al 1991, Arav & Zeron 1997, Isachenko et al 1998, including man (Kuleshova et al 1999, Yoon et al 2000. As vitrification does not require a programmed freezer and the technique itself is easy, safe and highly efficient, it will become an indispensable method in cryobiology in the future (Kuleshova & Lopata 2002, Liebermann et al 2002. Normal offspring have been produced from the vitrified mature (Kono et al 1991, Hamano et al 1992, Kuleshova et al 1999, Yoon et al 2000 and immature oocytes (Vieira et al 2002).…”
Section: Introductionmentioning
confidence: 99%
“…Recently, vitrification has been widely used to cryopreserve oocytes in many mammals (Kono et al 1991, Arav & Zeron 1997, Isachenko et al 1998, including man (Kuleshova et al 1999, Yoon et al 2000. As vitrification does not require a programmed freezer and the technique itself is easy, safe and highly efficient, it will become an indispensable method in cryobiology in the future (Kuleshova & Lopata 2002, Liebermann et al 2002. Normal offspring have been produced from the vitrified mature (Kono et al 1991, Hamano et al 1992, Kuleshova et al 1999, Yoon et al 2000 and immature oocytes (Vieira et al 2002).…”
Section: Introductionmentioning
confidence: 99%
“…The authors concluded that the number of single-embryo transfers with vitrified embryos was limited, and the results did not prove that vitrified embryos were more viable than slow frozen embryos. In the current study, we found that slow [9] and may have higher potential cell toxicity, which may be one of the major factors affecting development of embryos. Several studies have shown similar pregnancy and implantation rates between slow freezing and vitrification [13,27].…”
Section: Discussionmentioning
confidence: 53%
“…Vitrification obtains a higher embryo survival rate and fully intact blastomere rate compared with slow freezing [8]. However, vitrification uses high concentration of cryoprotectants [9] and there are still concerns regarding its safety. The effect of vitrification on embryo development potential and birth outcomes after vitrification still needs to be determined.…”
Section: Introductionmentioning
confidence: 99%
“…In fact, vitrification is based on embryo manipula-tion into different carrier tools applied to minimize the volume and to submerge the sample quickly into liquid nitrogen, allowing an ultrafast freezing speed, which avoids ice crystal formation, thus eliminating its deleterious effects in the cell [157]. This technique combines the use of small volumes with high concentration of two or more cryoprotectants [158] and it can be more adapted to IVP embryos [149,159,160].…”
Section: Vitrificationmentioning
confidence: 99%